Shear Bond Strength of Universal Adhesives with Different Methods of Zirconia Ceramic Preparation after Thermocycling: A Laboratory Study: Shear Bond Strength of Universal Adhesives to Zirconia - Yarmohammadi, Ebrahim; Kavousinejad, Shiva (Journal of Dental School, 2024)
Objectives The present study aimed to assess the level of shear bond strength (SBS) of universal adhesives (G-premio Bond Universal (GBU) and All Bond Universal (ABU) on zirconia without surface preparation, zirconia sandblasted by 50-micron aluminum oxide particles, and zirconia glazed by low-fusing ceramics after the thermocycling process. Methods Two Ceramill ZI zirconia blocks were used to prepare 18 cubes with dimensions of 10×10×10 mm. Then, based on the type of surface preparation, these 18 sintered zirconia cubes were classified into three groups of six, including the control group, sandblasted group, and glazed group. Each group was classified into two subgroups based on the type of universal adhesive (ABU/GBU). On each cube, four cylinders filled with Panavia F2 resin cement with a diameter of 1.5 mm and a height of 2 mm were attached by the universal adhesive of the related subgroup (n = 72). The samples were subjected to 5000 thermal cycles in the thermocycler, each sample was assessed to test SBS, and the type of failure observed in each group was finally observed under a stereomicroscope. The data were analyzed using a two-way analysis of variance (ANOVA) test, Tukey’s post hoc test, and independent t-test, with a significance level of 0.05. Results There was a statistically significant difference in SBS between the control group and the other two groups (p-value < 0.05). At the same time, there was no statistically significant difference between the sandblasted zirconia group and the glazed zirconia group (p-value = 0.13). Conclusion: Applying a low-fusing glazed layer to prepare the zirconia surface leads to an increased SBS of dual-cured self-etch resin cement, equivalent to sandblasting with 50-micron aluminum oxide after the thermocycling process.